2011, a year of records in the Peruvian Chemistry Olympiad (OPQ) - Chong, Miguel (2011)
The Peruvian Chemistry Olympiad (OPQ) set a new participation record, with over 2,000 students nationwide. Furthermore, the Peruvian National team achiev edits greatest success in the International Chemistry Olympiad (IChO) and the Iberoamerican Chemistry Olympiad (OIAQ), with a total of seven awards.